Proceedings of the Scientific-Practical Conference "Research and Development - 2016" - Anisimov, K. V.; Dub, A. V.; Kolpakov, S. K.; Lisitsa, A. V.; Petrov, A. N.; Polukarov, V. P.; Popel, O. S.; Vinokurov, V. A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is open access under a CC BY 4.0 license. It relates to the III Annual Conference hosted by the Russian Federal Ministry of Education and Science in December 2016. This event has summarized, analyzed and discussed the interim results, academic outputs and scientific achievements of the Russian Federal Targeted Programme for Research and Development in priority areas of development of the Russian Scientific and Technological Complex for 2014-2020. It contains 75 selected papers from 6 areas considered priority by the Federal programme: computer science, ecology & environment sciences; energy and energy efficiency; life sciences; nanoscience & nanotechnology; and transport & communications. The chapters report the results of the 3-years research projects supported by the Programme and finalized in 2016.
Multimodal Control System of Active Lower Limb Exoskeleton with Feedback -- Investigation and Development of Methods for Improving Robustness of Automatic Speech Recognition Algorithms in Complex Acoustic Environments -- Smart Endoscope-Firmware Complex for Real-Time Analysis and Recognition of Endoscopic Videos -- The Development of Constructive-Technological Decisions on Creation of a Family of Microelectronic Elements on the «Silicon on Insulator» (SOI) Structures to Provide the Ability to Create Sensors of External Inﬂuences of a Various Functional Purpose -- Thermopile IR Sensor Arrays -- Development Signal Processing Integrated Circuit for Position Sensors with High Resolution -- Brain-Controlled Biometric Signals Employed to Operate External Technical Devices -- Improving Talent Management with Automated Competence Assessment: Research Summary.
Keywords: Nanotechnology; Transportation engineering; Traffic engineering; Environment; Life sciences; Nanotechnology; Transportation Technology and Traffic Engineering; Environmental Sciences; Life Sciences